PENGARUH DESAIN INTERIOR TERHADAP KEPUTUSAN TAMU MEMILIH TRAVELLO HOTEL MANADO - Polikarpus Petrik Kebung; Bet El S. Lagarense; Agustinus Walansendouw (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2022)
The initial step of this research is conducting observation at the research location before determining the research topic related to the Influence of Interior Design Towards Guests Decisions to Choose Travello Hotel Manado. After finding the research problem and determining the topic, the research questionares were distributed t to the guest who used the servive at Travello Hotel Manado Field oservation and interview were conducted with the hotel management, staff and guest in order to find out to what extent was the influence of interior design has inflouenced the guests decision to choose Travello Hotel Manado. The results of calculation show that Y = 6,46 + 0,83 X which means that every incraese in varible X will result in an incrase in variable Y, and by using correlation coefficient analysis r = 0,94. The results showed that the correlation between varaible X and variable Y was strong enough with a value of nearly positive 1. Coefficient determinant r2=0,89 shows the variable of guests satisfication due to a sufficiently strong influence of interior design as much as 89% indicating variations of variable Y (Guests Decision to Choose Travello Hotel Manado) due to a sufficiently strong influence of interior design. Travello Hotel Manado should maintain its existence in service and comfort such as internal design to gain the guests loyalty in using the service at Travello Hotel Manado and not to choose the other hotels as competitirs.